Implementasi Algoritma Apriori Pada Data Penjualan Frisian Flag Di PT. Triyanto Sukses Mandiri Bandung - Devie Firmansyah; Muhamad Rhomi Nendriawan (Jurnal Komputer Bisnis, 2021)
Sales transaction data activity at PT. Triyanto Sukses Mandiri (TSM) Bandung is getting higher and higher, so that without realizing it this can cause accumulation of data, if left alone without processing the sales transaction data it will just become meaningless garbage. An application is needed to analyze the sales transaction data of the Frisian flag by using data mining as a data analysis technique that can help PT. Triyanto Sukses Mandiri obtained knowledge in the form of sales patterns within a certain month period. Data mining applications are built using linear sequential processes with the PHP programming language and MySQL database. The algorithm used as the main process of market basket analysis is the a priori algorithm using the minimum support parameters, minimum confidence, and the month period in sales transactions to find association rules. So that it can assist companies in analyzing patterns of sales transactions for what products are most in demand and improving marketing strategies.